1981
DOI: 10.1111/j.1476-5381.1981.tb09966.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mianserin, Desipramine and Maprotiline on Blood Pressure Responses Evoked by Acetylcholine, Histamine and 5‐hydroxytryptamine in Rats

Abstract: 1 In rats anaesthetized with pentobarbitone, intravenous administration of desipramine (0.1 mg/kg), maprotiline (0.5 mg/kg) or mianserin (0.3 -3.0 mg/kg) did not modify the blood pressure lowering effects of acetylcholine (0.25-1.0 pg/kg, i.v.) which were significantly reduced by atropine (3.0 pg/kg, i.v.). 4 In syrosingopine pretreated rats given mianserin 0.1 mg/kg, intravenously, 5-HT (20.0jpg/kg, i.v.) produced a significant fall in blood pressure which could be reduced by a large dose of mianserin (10.0 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 19 publications
2
11
0
Order By: Relevance
“…In pithed rats 5-HT produced a pure pressor response. These results are in agreement with data obtained by Cavero et al [21] and Kalkman et al [22], 5-HT2 receptors are responsible for the rise in blood pressure caused by 5-HT [16]. The results of the experiments described in the present paper show that the pressor response to serotonin was reduced in a dose-dependent manner by acute ethanol administration (table 1) and by the specific 5-HT2-antagonist ketanserin [22,23] (fig.…”
Section: Discussionsupporting
confidence: 83%
“…In pithed rats 5-HT produced a pure pressor response. These results are in agreement with data obtained by Cavero et al [21] and Kalkman et al [22], 5-HT2 receptors are responsible for the rise in blood pressure caused by 5-HT [16]. The results of the experiments described in the present paper show that the pressor response to serotonin was reduced in a dose-dependent manner by acute ethanol administration (table 1) and by the specific 5-HT2-antagonist ketanserin [22,23] (fig.…”
Section: Discussionsupporting
confidence: 83%
“…In our laboratory sero tonin usually produces a pure pressor re sponse [15,23] which is mainly due to the activation of 5-HTt receptors in vascular smooth muscle [15]. The results of experi ments described in the present paper showed that the pressor response to serotonin was reduced by the specific 5-HT2-antagonist ke tanserin [24,25] as well as by captopril in a dose-dependent manner ( fig.…”
Section: Discussionsupporting
confidence: 53%
“…Multiple investigators have demonstrated the ability of 5-HT, given either subcutaneously or intravenously, to decrease blood pressure in either rodents or dogs. In a pithed rat model, administration of 5-HT results in an increase in blood pressure (Cavero et al, 1981), suggesting that the interaction with the central sympathetic nervous system may be key for the mechanism of blood pressure decrease. There are few reports of the response of the human to 5-HT (intravenous), and in one study that addressed directly the effect of 5-HT on blood pressure in man, the effects of 5-HT on blood pressure were variable (Carlson et al, 1967).…”
Section: A Effects Of 5-hydroxytryptamine and Serotonergicmentioning
confidence: 99%